PENENTUAN AREA WAJAH MENGGUNAKAN ALGORITMA VIOLA-JONES UNTUK APLIKASI MANIPULASI WARNA CITRA DIGITAL - Rainhard, Rainhard; Mulyana, Teady Matius Surya (Jurnal Algoritma, Logika dan Komputasi, 2025)
Nowadays, many smartphones have a high-resolution camera module thus giving them ability to take photo and store it as digital image, with enormous size and dimension. Capturing photo with smartphone is also getting more common and some of the photo contain a subject of human face.The Objective of this research is to implementing the Viola-Jones Object Detection Algorithm to a colour manipulation application for digital image that has been produced by smartphone. Object Detection is a branch of Computer Vision that used to detect the presence of an object using feature or template. In this research, Viola-Jones will be used for detecting the presence of human face on a digital image. The Result of this research is that the Viola-Jones Object Detection Algorithm can be implemented to the digital image colour manipulation application. This application can detect the presence of human face on the digital image.The Conclusion of this research is that Viola-Jones algorithm is able to detect the presence of human face on the smartphone-produced digital image with 93% detection accuracy, based on the ratio of the total amount of face detected by the total amount of real face presence. Proven with the testing of  20 types of digital image with one face, and many faces.